A Philosophical Critique of Instrumentalism in Islamic Education: Analyzing Syed Muhammad Naquib Al-Attas’ Perspective - Akhsani Ulvatun Ni'mah; Asnawan Asnawan (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2026)
The instrumentalization of education has an impact on the reduction of educational objectives, which should be based on the development of all human potential, namely, intellectual, moral, and spiritual dimensions. Studies on the instrumentalization of education generally focus only on pedagogical and practical aspects, while philosophical analysis remains relatively under-researched. This article examines the implications of Syed Muhammad Naquib Al-Attas's thinking for the objectives of Islamic education, focusing on the problem of the instrumentalization of education through philosophical (ontological, epistemological, and axiological) analysis. This study uses a library research method with a conceptual analysis of Al-Attas's works and relevant literature. The results of the study show that the instrumentalization of education stems from ontological errors in understanding the meaning and essence of humanity, leading to an epistemological narrowing that has given rise to a utilitarian axiology. As a constructive alternative foundation, Al-Attas emphasizes the concept of ta’dib through the internalization of Islamic education, which understands the meaning of knowledge as a means of forming civilized and holistic human beings. This study highlights the significance of Al-Attas's ideas in redefining the objectives of Islamic education in the modern era.